Effect of the reduction in training volume during the COVID-19 era on performance in 100-m and 400-m freestyle events in Greek swimming championships - Tsalis, G.; Mougios, V. (Sports, 2022)
The COVID-19 pandemic had a profound impact on almost all social activities, including sport participation. Swimming training was greatly reduced during the 2019-2020 and 2020-2021 seasons (by four and two months, respectively), which caused athletes and coaches to worry about performance in championships. The present study investigated the impact of COVID-19 lockdowns on the results of Greek swimming championships in the categories of 13 to 18 years of age during 2020 and 2021. Forty-one coaches were interviewed about the training process (satisfaction, duration of the training season, and daily training swimming distance), and the performance of swimmers in national championships over seven seasons (2014-2021) was analyzed. The duration of the training season and the daily swimming distance, as reported by the coaches, were lower during the 2019-2020 and 2020-2021 seasons, compared to the previous five seasons (p < 0.001). The number of swimmers who achieved qualifying times for the national championships during the COVID-19 era were similar to those in previous years. Comparisons of the times in the 100-m and 400-m freestyle events, in both genders, from 2015 through 2021, showed no significant differences except for the 400-m event in males, in which a lower performance was detected in 2021 compared to 2015 (by 2.7%, p = 0.001). In conclusion, two or four months of detraining during the COVID-19 era had a negative impact on the coaches` evaluation of the training process, but there was no effect on the number of young swimmers who qualified for the national championships and a negligible effect on swimming performance in 100-m and 400-m freestyle events.